The Academic Resilience Scale (ARS-30): A New Multidimensional Construct Measure - Cassidy, Simon (Frontiers in Psychology, 2016)
Resilience is a psychological construct observed in some individuals that accounts for success despite adversity. Resilience reflects the ability to bounce back, to beat the odds and is considered an asset in human characteristic terms. Academic resilience contextualises the resilience construct and reflects an increased likelihood of educational success despite adversity. The paper provides an account of the development of a new measure of academic resilience. The 30 item Academic Resilience Scale (ARS-30) explores process—as opposed to outcome—aspects of resilience, providing a new multidimensional construct measure of academic resilience based on students’ specific adaptive cognitive-affective and behavioural responses to academic adversity. Findings from the study involving a sample of undergraduate students (N=532) demonstrate that the ARS-30 has good internal reliability and construct validity. It is suggested that a measure such as the ARS-30, which is based on adaptive responses, aligns more closely with the conceptualisation of resilience and provides a valid construct measure of academic resilience relevant for research and practice in university student populations.